2016 թ. Ապրիլյան պատերազմի արձագանքը Բեյրութի «Ազդակ» օրաթերթում - Օհանյան, Տատյանա (ՀՀ ԳԱԱ Պատմության ինստիտուտ)
The April 2016 war received wide coverage in the “Azdak” daily newspaper published in Beirut. The newspaper covers events taking place in Karabakh and Armenia, based on received news, information and publications of foreign media. “Azdak” publications show that the newspaper takes a pro-Armenian position. “Azdak” regularly covers the military actions of the April war, the reaction of the international community and emphasizes the Armenia-Artsakh-Diaspora trinity. From a legal point of view, it calls for international recognition of Artsakh in the Karabakh negotiation process, as well as for the recognition of Azerbaijan as a terrorist state by the international community. “Azdak” considers it necessary to sign a military agreement on mutual assistance between the Republic of Armenia and the Republic of Artsakh and presents the procedure for signing the agreement. Comparing the work of international reporters, “Azdak” emphasizes that the Armenian side does not create obstacles for the reporter, and the Azerbaijani side not only creates obstacles, but also dayot or directions.
Keywords: Պարբերականներ